Tracing time through cuticular clues: the role of rearing conditions and generational divergence in Lucilia sericata (Meigen, 1826) (Diptera: Calliphoridae) - Kula, Canan; Moore, Hannah (Turkish Entomological Society, 2025)
The chemical profiles of the cuticle of adult flies are highly influenced by environmental factors and generational variation, although the extent and mechanisms of these influences are still poorly understood. This research rigorously investigates the influence of rearing environment and generational changes on the cuticular hydrocarbon (CHC) profiles of adult flies collected from the natural environment in Swindon (UK), in June 2019. Gas chromatography-mass spectrometry (GC-MS) was used to analyze the hydrocarbon profiles. Then, chemometric analysis was applied to determine the chemical variation patterns, allowing the samples to be classified according to their chemical fingerprints. Significant differences in hydrocarbon composition were found between laboratory-maintained and field-collected specimens, underscoring the impact of environmental conditions on CHC expression. Additionally, gradual modifications in hydrocarbon content were detected across generations raised in the controlled environment, suggesting the involvement of adaptive physiological or epigenetic mechanisms. These findings contribute valuable insights into cuticle plasticity, highlighting its relevance in forensic entomology, chemical ecology, and insect evolutionary biology. The implications also extend to forensic investigations, where cuticular hydrocarbon profiles (CHCs) demonstrate potential for enhancing postmortem interval (PMI) estimation accuracy and species identification in criminal cases. By demonstrating quantifiable differences in CHC composition across rearing conditions and generations (AUC values ≥0.92 for all comparisons), this study provides a foundation for the broader application of chemical markers in forensic investigations.
Keywords: 31 Biological Sciences; 3103 Ecology; 34 Chemical Sciences; Generation differences; hydrocarbons; rearing conditions